1980
DOI: 10.1002/bbpc.19800840303
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of a Binary Solidus from the Liquidus and Minimal Additional Thermodynamic Information

Abstract: In a binary system, if the liquidus has been measured, if the thermodynamic properties of the liquid phase are known, and if the entropy of the solid phase is known or may be assumed to be ideal, then an exact thermodynamic calculation of the solidus as well as of the enthalpy of the solid can be made. The equations are derived and sample calculations are made for several systems. General relationships between binary phase diagrams and the thermodynamic properties of the phases are then developed. It is shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Since it has been reported that Mn does not dissolve in Y(HCP), [16] these two measured points are almost certainly in error because they violate the limiting liquidus slope rule. [21] Figure 4 shows the enthalpy of formation of intermetallic compounds. Calorimetrically determined data by Pisch et al [19] are compared with calculations from the present optimization and from those of Flandorfer et al [16] and Gröbner et al [17] As seen in the figure, the measured enthalpy of formation of Mn 2 Y is higher than the average of Section I: Basic and Applied Research Basic and Applied Research: Section I the enthalpies of Mn 23 Y 6 and Y(HCP).…”
Section: The Mn-y Systemmentioning
confidence: 99%
“…Since it has been reported that Mn does not dissolve in Y(HCP), [16] these two measured points are almost certainly in error because they violate the limiting liquidus slope rule. [21] Figure 4 shows the enthalpy of formation of intermetallic compounds. Calorimetrically determined data by Pisch et al [19] are compared with calculations from the present optimization and from those of Flandorfer et al [16] and Gröbner et al [17] As seen in the figure, the measured enthalpy of formation of Mn 2 Y is higher than the average of Section I: Basic and Applied Research Basic and Applied Research: Section I the enthalpies of Mn 23 Y 6 and Y(HCP).…”
Section: The Mn-y Systemmentioning
confidence: 99%
“…The liquidus at Mn-rich side in the phase diagram suggested by Kirchmayr and Lugscheider [22] are also unlikely to happen from the viewpoint of the limiting slope rule. [47] The enthalpy data of Ivanov et al [45] were not available at that time. Consequently, the calculated integral and partial enthalpies of mixing at 1723 K from Wang et al [26] are notably different from the data of Ivanov et al [45] as shown in Fig.…”
Section: The Mn-dy Systemmentioning
confidence: 97%
“…It should be also noted that the experimental data [21] in the liquidus of Mn-rich side is less acceptable from the viewpoint of the limiting slope rule. [47] The calculated invariant reactions are tabulated in Table 4 in comparison to the experimental data.…”
Section: The Mn-tb Systemmentioning
confidence: 99%